Literature Review: Pengaruh Digital Marketing dan Electronic Word of Mouth (E-WOM) Terhadap Niat Beli dengan Brand Image Sebagai Variabel Mediasi - Dwi Prasetyono Nugroho (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Technological transformation in Indonesia, particularly the growth in internet users, has created significant opportunities for the implementation of digital marketing. Based on a literature review of ten journal articles, it was found that digital marketing and electronic word-of-mouth (e-WOM) play a significant role in influencing consumers' purchase intentions. Moreover, a positive brand image can strengthen this influence by building consumer trust in products. The studies also reveal that brand image may mediate the relationship between digital marketing and purchase intention, although variations in findings were noted across different studies. In conclusion, this review highlights the importance of integrating digital marketing, e-WOM, and brand image into marketing strategies to enhance purchasing decisions. Further research is encouraged to explore other aspects of digital marketing more comprehensively and to conduct path analysis to better understand the interactions among these variables.